2005
DOI: 10.1111/j.1526-4610.2005.05053_3.x
|View full text |Cite
|
Sign up to set email alerts
|

Migraine Accompanied by Hemifacial Spasm: A Case Report

Abstract: A 36-year-old woman has had repeated episodes of concurrent hemifacial spasm and migraine for 8 years. Her history is summarized and possible pathophysiologic links are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
9
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…At least two patients with concurrent HFS and ipsilateral migraine have been observed: that reported by Husid (5) and the one reported here. A pathophysiological link rather than a coincidental co-occurrence seems likely, since both phenomena have been coupled for many years in each patient.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…At least two patients with concurrent HFS and ipsilateral migraine have been observed: that reported by Husid (5) and the one reported here. A pathophysiological link rather than a coincidental co-occurrence seems likely, since both phenomena have been coupled for many years in each patient.…”
Section: Discussionsupporting
confidence: 62%
“…In fact, the appearance of abnormal movements is not included among the potential features of migraine attacks in the International Headache Society classification (4). Recently, the case of a woman having repeated episodes of concurrent hemifacial spasm (HFS) and migraine has been reported (5). We also describe here a patient with unilateral migraine associated with ipsilateral HFS and provide some additional findings that might point to possible pathophysiological mechanisms.…”
mentioning
confidence: 99%
“…Cluster headache is postulated to be associated with an abnormal interaction between trigeminal afferents and cranial parasympathetic efferents. Trigeminal afferent input alters the excitability of facial motoneurons in HFS 67–69. In our series, 6 patients had associated migraine, and 1 patient had trigeminal neuralgia, possibly indicative of increased excitability of brain stem nuclei.…”
Section: Discussionmentioning
confidence: 62%
“…It has been suggested that migraine could map or remap to a site of trigeminal nerve injury (11,12). Thus, in rare instances, the origin of the trigeminal nerve might become involved by the migraine mechanism, as can occur with the oculomotor nerves in ophthalmoplegic migraine (13) and the facial nerve in migrainous facial palsy and hemifacial spasm (1416). These two patients suggest a reciprocal link, with the migraine mechanism activating the trigeminal nerve to facilitate neuralgic pain and vice versa.…”
Section: Discussionmentioning
confidence: 99%